CXCR2 Blockade Mitigates Neural Cell Injury Following Preclinical Chorioamnionitis - Yellowhair, Tracylyn R.; Newville, Jessie C.; Noor, Shahani; Maxwell, Jessie R.; Milligan, Erin D.; Robinson, Shenandoah; Jantzie, Lauren L. (Frontiers in Physiology, 2019)
Minimizing central nervous system (CNS) injury from preterm birth depends upon identification of the critical pathways that underlie essential neurodevelopmental and CNS pathophysiology. While chorioamnionitis (CHORIO), is a leading cause of preterm birth, the precise mechanism linking prenatal brain injury and long-term CNS injury is unknown. The chemokine (C-X-C motif) ligand 1 (CXCL1) and its cognate receptor, CXCR2, are implicated in a variety of uterine and neuropathologies, however, their role in CNS injury associated with preterm birth is poorly defined. To evaluate the putative efficacy of CXCR2 blockade in neural repair secondary to CHORIO, we tested the hypothesis that transient postnatal CXCR2 antagonism would reduce neutrophil activation and mitigate cerebral microstructural injury in rats. To this end, a laparotomy was performed on embryonic day 18 (E18) in Sprague Dawley rats, with uterine arteries transiently occluded for 60 min, and lipopolysaccharide (LPS, 4µg/sac) injected into each amniotic sac. SB225002, a CXCR2 antagonist (3mg/kg), was administered intraperitoneally from postnatal day 1 (P1)-P5. Brains were collected on P7 and P21 and analyzed with western blot and ex vivo diffusion tensor imaging (DTI). Results demonstrate that transient CXCR2 blockade reduced cerebral neutrophil activation (myeloperoxidase expression/MPO) and mitigated connexin43 expression, indicative of reduced neuroinflammation at P7 (p<0.05 for all). CXCR2 blockade also reduced alpha II-spectrin calpain-mediated cleavage, improved pNF/NF ratio, and minimized Iba1 and GFAP expression consistent with improved neuronal and axonal health and reduced gliosis at P21. Importantly, DTI revealed diffuse white matter injury and decreased microstructural integrity following CHORIO as indicated by lower fractional anisotropy (FA) and elevated radial diffusivity (RD) in major white matter tracts (p<0.05). Early postnatal CXCR2 blockade also reduced microstructural abnormalities in white matter and hippocampus at P21 (p<0.05). Together, these data indicate that transient postnatal blockade of CXCR2 ameliorates perinatal abnormalities in inflammatory signaling, and facilitates neural repair following CHORIO. Further characterization of neuroinflammatory signaling, specifically via CXCL1/CXCR2 through the placental-fetal-brain axis, may clarify stratification of brain injury following preterm birth, and improve use of targeted interventions in this highly vulnerable patient population.